Lung transplantation following controlled hypothermic storage with a portable lung preservation device: first multicenter European experience - Provoost, An-Lies; Novysedlak, Rene; Van Raemdonck, Dirk; Van Slambrouck, Jan; Prisciandaro, Elena; Vandervelde, Christelle M.; Barbarossa, Annalisa; Jin, Xin; Denaux, Karen; De Leyn, Paul; Van Veer, Hans; Depypere, Lieven; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Compared with traditional static ice storage, controlled hypothermic storage (CHS) at 4–10°C may attenuate cold-induced lung injury between procurement and implantation. In this study, we describe the first European lung transplant (LTx) experience with a portable CHS device. Methods A prospective observational study was conducted of all consecutively performed LTx following CHS (11 November 2022 and 31 January 2024) at two European high-volume centers. The LUNGguard device was used for CHS. The preservation details, total ischemic time, and early postoperative outcomes are described. The data are presented as median (range: minimum–maximum) values. Results A total of 36 patients underwent LTx (i.e., 33 bilateral, 2 single LTx, and 1 lobar). The median age was 61 (15–68) years; 58% of the patients were male; 28% of the transplantations had high-urgency status; and 22% were indicated as donation after circulatory death. In 47% of the patients, extracorporeal membrane oxygenation (ECMO) was used for perioperative support. The indications for using the CHS device were overnight bridging (n = 26), remote procurement (n = 4), rescue allocation (n = 2), logistics (n = 2), feasibility (n = 1), and extended-criteria donor (n = 1). The CHS temperature was 6.5°C (3.7°C–9.3°C). The preservation times were 11 h 18 (2 h 42–17 h 9) and 13 h 40 (4 h 5–19 h 36) for the first and second implanted lungs, respectively, whereas the total ischemic times were 13 h 38 (4 h 51–19 h 44) and 15 h 41 (5 h 54–22 h 48), respectively. The primary graft dysfunction grade 3 (PGD3) incidence rates were 33.3% within 72 h and 2.8% at 72 h. Intensive care unit stay was 8 (4–62) days, and the hospital stay was 28 (13–87) days. At the last follow-up [139 (7–446) days], three patients were still hospitalized. One patient died on postoperative day 7 due to ECMO failure. In-hospital Clavien–Dindo complications of 3b were observed in six (17%) patients, and 4a in seven (19%). Conclusion CHS seems safe and feasible despite the high-risk recipient and donor profiles, as well as extended preservation times. PGD3 at 72 h was observed in 2.8% of the patients. This technology could postpone LTx to daytime working hours. Larger cohorts and longer-term outcomes are required to confirm these observations.